Human vs Machine: A Comparative Effectiveness of A Particular Technique and AI Tools in Improving Writing Skills - Delfia Herwanis; Rahmanita Zakaria; Rusmiati Rusmiati; Sungkawati Sukardi Wahyuningsih (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
The research paper titled